2000
DOI: 10.4049/jimmunol.164.9.4659
|View full text |Cite
|
Sign up to set email alerts
|

Stat4 Is Expressed in Activated Peripheral Blood Monocytes, Dendritic Cells, and Macrophages at Sites of Th1-Mediated Inflammation

Abstract: Stat4 is a key transcription factor involved in promoting cell-mediated immunity, whose expression in mature cells has been reported to be restricted to T and NK cells. We demonstrate here, however, that Stat4 expression is not restricted to lymphoid cells. In their basal state, monocytes do not express Stat4. Upon activation, however, IFN-γ- and LPS-treated monocytes and dendritic cells express high levels of Stat4. Monocyte-expressed Stat4 in humans is phosphorylated in response to IFN-α, but not IL-12. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
113
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(125 citation statements)
references
References 23 publications
6
113
0
3
Order By: Relevance
“…Furthermore, STAT4 protein was found in human dendritic cells, monocytes, and macrophages (18,19). Therefore, we envisaged a role of STAT4 in macrophage activation by IL-12 plus IL-18.…”
Section: Macrophage Stimulation With Il-12 Plus Il-18 Leads To Strongmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, STAT4 protein was found in human dendritic cells, monocytes, and macrophages (18,19). Therefore, we envisaged a role of STAT4 in macrophage activation by IL-12 plus IL-18.…”
Section: Macrophage Stimulation With Il-12 Plus Il-18 Leads To Strongmentioning
confidence: 99%
“…In contrast, in human blood monocyte-derived dendritic cells stimulation with IL-12 led to tyrosine-phosphorylation of Tyk2 and Jak2 kinase as well as of STAT3 and STAT4 (18). In LPS-activated human monocytes, STAT4 protein was shown to be expressed and tyrosine-phosphorylated on stimulation with IFN-␣ (19). However, whether NF-B, NOS2, and/or the Jak/STAT pathway are actually required for the production of IFN-␥ by dendritic cells or macrophages is unknown to date.…”
mentioning
confidence: 99%
“…In contrast to the findings of Lighvani et al (42), where human monocytes treated with IFN-␥ expressed substantial levels of T-bet, we did not detect T-bet expression in peritoneal, splenic, or BM-derived macrophages after treatment with IFN-␥ or after phagocytosis of latex beads (data not shown), leading us to conclude that the production of IFN-␥ from these cells is controlled by transcription factors other than T-bet. One of these factors may well be Stat4 (46)(47)(48). Substantial differences in lineage commitment and subset profiles of DCs and macrophages have been observed between human and mouse species (5).…”
Section: T-bet Expression In Murine Dcsmentioning
confidence: 99%
“…AR-R17779 is a more selective ␣7nAChR agonist, with a 35,000-fold higher selectivity and 5-fold higher affinity for the ␣7nAChR compared with nicotine (41,42). Previous in vivo studies have indicated that nicotine and ␣7-specific agonists have antiinflammatory properties.…”
mentioning
confidence: 99%